Apparatus vs. Neutrality: When the Police are Called the Brown Party in Indonesian Political Narratives - Amin Amin; Muhammad Putra Sholeh Hardjono; Ida Hindarsah (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
The term "Brown Party" emerged as a public criticism of the alleged lack of impartiality of the police in the political contestation leading up to the 2024 regional elections. The color brown refers to police uniforms and is used to criticize officers perceived as biased. This study uses Robert Entman's framing theory to analyze how the "Brown Party" narrative is shaped by the media and political elite, and its impact on public trust and democratic legitimacy. The analysis shows that certain framings reinforce perceptions. public will partisanship apparatus, Which impact on increasing criticism towards state institutions in public spaces.